2002
DOI: 10.1023/a:1016503804742
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Maitake mushroom has been reported to favorably influence hypertension and diabetes mellitus. The purpose of this study was to compare the effects of whole Maitake mushroom powder and two extracts designated as ether soluble (ES) and water soluble (WS) on Zucker fatty rats (ZFR), a model of insulin resistance, and on spontaneously hypertensive rats (SHR), a model of genetic hypertension. In the initial study, we followed four groups of eight ZFR and SHR receiving special diets: a baseline diet (BD), BD + whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Studies have been carried out to test plasma TAG-lowering effect by adding mushroom powder into the diets. The results varied, where studies showed a significant effect of lowering plasma TAG [14, 15, 18, 28, 29], whilst other did not [17, 30, 31]. There are a few factors that may explain these differing results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been carried out to test plasma TAG-lowering effect by adding mushroom powder into the diets. The results varied, where studies showed a significant effect of lowering plasma TAG [14, 15, 18, 28, 29], whilst other did not [17, 30, 31]. There are a few factors that may explain these differing results.…”
Section: Discussionmentioning
confidence: 99%
“…Many varieties of mushrooms have been reported to possess antihyperglycemic activity through various mechanism like glucose/insulin metabolism and/or by enhancing peripheral insulin sensitivity (9,30) or by enhancing insulin release by Islets of Langerhans (8,31). Insulin-releasing and insulin-like activity in A. campestris (a variety of mushroom) is reported earlier (8).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mushroom species such as Lentinula edodes , Ganoderma lucidum , Grifola frondosa , Pleurotus cornucopiae , and Pleurotus nebrodensis have antihypertension activities; moreover, their mechanisms of action have been suggested to involve the decrease blood pressure by improvement in blood levels of triglyceride and cholesterol as well as kidney function and inhibition of angiotensin-converting enzymes [3, 4, 27, 28]. However, this is the first report to indicate an antihypertensive mechanism involving an improvement in endothelial signaling due to mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Some mushrooms have been used in Chinese medicine and folk medicine for a long time. Recently published reports have demonstrated that various kinds of mushrooms have beneficial effects on blood pressure [36]. Sparassis crispa ( S. crispa ) is an edible mushroom that has recently been cultivated in Japan.…”
Section: Introductionmentioning
confidence: 99%